Isolation and characterization of EgGST, a glutathione S-transferase protein transcript in oil palm (Elaeis guineensis Jacq.) - Conie, Toh; Namasivayam, Parameswari; Ho, Chai Ling; Syed Alwee, Sharifah Shahrul Rabiah (Universiti Putra Malaysia Press, 2015)
The formation of callus and somatic embryos remains one of the major bottlenecks in oil palm tissue culture. Unlike other crops, oil palm tissue culture is a very slow process. In the present study, EgGST (GenBank accession no. AIC33066.1), an oil palm gene coding for a putative glutathione S-transferase protein, has been characterized molecularly. The full length cDNA sequence of EgGST isolated from oil palm cultured leaf explants at the 6th week is 1002 bp in length, with an Open Reading Frame (ORF) of 651 bp. The deduced EgGST encodes a 216-amino-acid protein with a predicted molecular mass of 23.68 kD and a pI value of 6.16. Its protein sequence shares 63% identity with the glutathione s-transferase gstf2 from Oryza sativa Indica Group (GenBank accession no. ABR25713.1) and contains thioredoxin fold and chloride channel domain. Real-time RT-PCR results showed that the EgGST transcript was differentially expressed across a time series of fortnightly-cultured leaf explants and had a higher transcript levels in nodular callus (NC) compared to friable callus (FC) for oil palm ortet of clone 4178. EgGST was also found to be preferentially expressed in all tissue culture derived materials except for oil palm cell suspension culture (CSC), whereas there were almost negligible expressions in all the non-tissue culture derived materials, except for root. Hence, it can be suggested that EgGST transcript may possibly be regulated differently at different stages of tissue culture and various tissues. Interestingly, EgGST also displayed a tissue-specific expression pattern via RNA in situ hybridization. To our knowledge, this is the first reported study on the analysis of the localization of target mRNA transcript of EgGST in different oil palm tissues. We postulated that EgGST might play significant roles at different stages of oil palm callogenesis, and could potentially be a candidate marker for oil palm callogenesis.